Appreciating the wrongfulness of criminal conducts: implications for the age of criminal responsibility - Wagland, Paul (Legal and criminological psychology, 2017)
Purpose. Although the ability to appreciate the wrongfulness of criminal conduct and to distinguish it from childish mischief forms the basis of Age of Criminal Responsibility (ACR) legislation in many countries, empirical research on the extent to which children possess this ability is limited. It was the aim of this study to investigate this issue. Methods. A total of 132 males and females from four age groups (8, 12, and 16 years and adults) participated in the study. Participants listened to a series of vignettes which described a person committing a transgression. The seriousness of the transgressions varied across vignettes. Participants then provided ratings on the wrongfulness and outcome expectations associated with the conduct described in the vignette. Results. Participants from all age groups evaluated criminal conduct more negatively than mischievous conduct. Participants from all age groups also anticipated more negative self-reactions, more negative reactions from peers, and more severe legal sanctions for criminal conduct. Conclusions. Eight-year-olds from the study sample demonstrated that they meet the current cognitive standard associated with achieving the ACR. These 8-year-olds also provided evidence that they were comparable to older children and adults in terms of their understanding of the wrongfulness of criminal behaviour and the ability to distinguish it from mischievous behaviour.